Utilizing the diversity of arbuscular mycorrhizal fungi and sweet potato leaf litter for the growth and production of andrographolide compounds in Andrographis paniculata - SUHARNO SUHARNO; AYU CAHYANINGSIH; PUGUH SUJARTA; TRI GUNAEDI; IGN. JOKO SUYONO; DIRK Y. P. RUNTUBOI; SUPENI SUFAATI (Society for Indonesian Biodiversity, 2024)
Abstract. Suharno, Cahyaningsih A, Sujarta P, Gunaedi T, Suyono IJ, Runtuboi DYP, Sufaati S. 2024. Utilizing the diversity of arbuscular mycorrhizal fungi and sweet potato leaf litter for the growth and production of andrographolide compounds in Andrographis paniculata. Biodiversitas 25: 1427-1435. This research aims to determine the effect of AMF diversity and the leaf litter of sweet potato on the growth and production of andrographolide compounds in sambiloto (Andrographis paniculata Nees.). Factorial analysis in a completely randomized experimental design with two factors and six replicates was used in this research. The factors consisted of the AMF inoculation (non-mycorrhizal, the inoculation with Glomus sp1, Glomus sp2, and Glomus aggregatum) and the addition of sweet potato leaf litter (without litter, with 5, 10, and 15 g per polybag). The results showed that AMF inoculation significantly increased plant height, number of leaves, leaf area, and biomass. Likewise, the addition of sweet potato leaf litter also affected the plant growth in all parameters. The combination between AMF inoculation and leaf litter addition contributes positively to the overall plant growth. The highest growth was noted in the plant inoculated with Glomus sp2 grown in the media added with 10 g of leaf litter per polybag. The inoculation of an indigenous AMF, Glomus sp2, could enhance the andrographolide compound content by 3.65%. AMF, thus, has the potential to improve the growth and content of andrographolide compounds in A. paniculata.